Re-estimation of thermal contact resistance considering near-field thermal radiation effect. (5th July 2019) - Xian, Yaoqi; Zhang, Ping; Zhai, Siping; Yang, Peipei; Zheng, Zhiheng
Highlights: The thermal contact resistance is re-estimated considering the radiation effect. The fluctuational electrodynamics calculation is performed for radiation effect on non-contact area. The thermal contribution between contact area and non-contact area is analyzed. Abstract: Thermal contact has always been a hot issue in many engineering fields and thermal contact resistance (TCR) is one of the important indicators weighing the heat transfer efficiency among the interfaces. In this paper, the contact heat transfer of conforming rough surfaces is theoretically re-estimated considering both the heat transfer from contact and non-contact regions. The fluctuational electrodynamics (an ab initio calculation) is adopted to calculate the thermal radiation. The contribution of the contact regions is estimated by the CMY TCR model and further studied by modelling specific surfaces with the corresponding surface roughness power spectrum. Several tests are presented where aluminum and amorphous alumina are mainly used in the simulations. Studies showed that there exists a significant synergy between the thermal conduction and near-field thermal radiation at the interface within a certain range of the effective roughness. When the effective roughness is near to the scales of submicron, the near-field thermal radiation effect should not be neglected even at room temperature.